The Effect of Lactobacillus Casei and Sucrose Concentrations on the Microbiology and Chemical Characteristics of Tofu Waste-Based Probiotic Drinks - Irmayanti, Irmayanti; Hakim, Lukmanul; Makmur, Teuku; Rizki, Paqrul; Ar, chairuni (Universitas Serambi Mekkah, 2020)
One industry that produces waste is tofu industry which produces solid waste and liquid waste from the washing, soaking, and cooking processes. To increase the added value of tofu industrial waste, tofu liquid waste can be used as a probiotic drink because it still contains relatively high protein in food processing.Making probiotic drinks from tofu wastewater requires the addition of carbohydrates in the form of sucrose. This research used factorial completely randomized design(CRD) consisting of two factors. The first factor was the addition ofsucrose (S) consisting of 3 levels:S1 = 10%, S2 = 12%, S3 = 14%.The second factor was the concentration of lactobacillus casei consisting of 3 levels: L1 = 4%, L2 = 7%, L3 = 10%.The addition of sucrose (S) was found to have a very significant effect on the total microbes, total acid, but have no significant effect on thepH of tofu liquid waste probiotic drink. The best treatment of probiotic drinks was that resulting from the addition of 10% sucrose and a concentration of Lactobacillus casei 7% (S1L) to produce good quality probiotic drinks with chemical properties, namely lactic acidbacteria 4.88, with pH of 3.57%, and total acid of 1.84%.Keywords: probiotic, lactobacillus casei, sucrose, tofu waste.